Change, concepts and the conceptualising method - Henriksen, Lars Bo (Proceedings of Pragmatic Constructivism, 2017)
When looking for theories and methods in social science able to describe and understand changes, pragmatic constructivism offers some possibilities in doing exactly that. Research on pragmatic constructivism requires dialogues with actors in the field and an emphasis on language and language development. Concepts and concept development therefore plays a very central role in any researchers effort to describe and understand changes in language games and life worlds. In this essay I will take a closer look the concept of concepts and at concept formation. Through an analysis of Nørreklit’s (1973) ideas of concepts as properties and Gadamer’s (1962) ideas of concept formation, it is concluded that concept development are present in everyday life as well as a research method. The difference between the two is the accidental processes of everyday life, while research methods require a conscious application of concept development.